Aplikasi Bimbingan Konseling Berbasis Web di Smp Negeri 1 Teras Boyolali - Murni, Murni; Susilo, Dahlan; Al Haris, Firdhaus Hari Saputro (Universitas Muhammadiyah Surakarta, 2015)
Duties and functions of Guidance and Counseling in the prevention and management of student violations of Junior High School is very important. However the reality of control and management of student violations in Junior High School Negeri 1 Teras is still done manually. In the digital age it is better control and management by using an integrated system by utilizing information and communication technology. This is way to facilitate stakeholders in monitoring control and management of student violations. The purpose of this study, the design of the application guidance and counseling in Junior High School Negeri 1 Teras Boyolali. This application is designed use PHP programming language and using MySQL database storage. Application Guidance Counseling is also accompanied by SMS Gateaway system for the delivery of information to the parents.